Talaromyces marneffei simA Encodes a Fungal Cytochrome P450 Essential for Survival in Macrophages - Kylie J. Boyce (American Society for Microbiology, 2018)
ABSTRACT Fungi are adept at occupying specific environmental niches and often exploit numerous secondary metabolites generated by the cytochrome P450 (CYP) monoxygenases. This report describes the characterization of a yeast-specific CYP encoded by simA ("survival in macrophages"). Deletion of simA does not affect yeast growth at 37°C in vitro but is essential for yeast cell production during macrophage infection. The ΔsimA strain exhibits reduced conidial germination and intracellular growth of yeast in macrophages, suggesting that the enzymatic product of SimA is required for normal fungal growth in vivo. Intracellular ΔsimA yeast cells exhibit cell wall defects, and metabolomic and chemical sensitivity data suggest that SimA may promote chitin synthesis or deposition in vitro. In vivo, ΔsimA yeast cells subsequently lyse and are degraded, suggesting that SimA may increase resistance to and/or suppress host cell biocidal effectors. The results suggest that simA synthesizes a secondary metabolite that allows T. marneffei to occupy the specific intracellular environmental niche within the macrophage. IMPORTANCE This study in a dimorphic fungal pathogen uncovered a role for a yeast-specific cytochrome P450 (CYP)-encoding gene in the ability of T. marneffei to grow as yeast cells within the host macrophages. This report will inspire further research into the role of CYPs and secondary metabolite synthesis during fungal pathogenic growth.